Terapeutic gardens - Mulé, Cinzia (2015)
Gardens have always been considered only as purely recreational places, like parks or simple garden rooms. The healing power that ornamental plants may have is rarely considered. What effects do they have when located in a medical facility? Those effects have been studied since the 80s and the positive results obtained are scientifically proven. Their use is becoming more indispensable each day in order to lower costs and the hospitalization time of patients, and also to improve their life quality when long-term care is required. The fundamental elements that a landscape designer must know and should take into account to make a good project are the subject matter of this paper.